Unraveling the Implementation of ASN Talent Management from the Vortex of Political Currents - Sunandar, Cucu; Meilawati, Nita; Khaeriyah, Yoyoh; Sumiati, Emi; Siswoyo, Mukarto; Hidayat, Moh. Taufik (Politeknik Siber Cerdika Internasional, 2024)
The article examines the implementation of talent management policies for State Civil Apparatus (ASN) in Kuningan Regency. Through a qualitative research approach using in-depth interviews and documentation studies, the authors analyze how talent management policies are implemented at the regional level. The results of the study show the implementation of the policy faces several challenges, including the issue of political intervention, limited resources and lack of awareness of the importance of talent management. However, several steps have been taken to improve the implementation of this policy, such as training and apparatus development. Continuous improvement efforts are needed to improve the implementation of talent management policies for ASN in Kuningan Regency to create quality, transparent, responsive, inclusive, and accountable public services and can support the achievement of better development goals.